2015
DOI: 10.1016/j.neuroscience.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates neurogenesis in the central canal during experimental autoimmune encephalomyelitis

Abstract: Nicotine has been shown to attenuate experimental autoimmune encephalomyelitis (EAE) through inhibiting inflammation in microglial populations during the disease course. In this study, we investigated whether nicotine modified the regenerative process in EAE by examining nestin-expressing neural stem cells (NSCs) in the spinal cord, which is the primary area of demyelination and inflammation in EAE. Our results show that the endogenous neurogenic responses in the spinal cord after EAE are limited and delayed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In spinal cord gray matter by contrast, we observed increased Olig2+ OPCs in mice consuming HFHS at 14 and 30 dpi. Since prior studies have shown that the central canal region is a potential source of OPCs ( Gao et al, 2015 ), it is possible that the increase in Olig2+ OPCs in spinal cord gray matter after SCI, but the reduction in white matter, reflects an impairment in the migration of newly generated OPCs. Also, we cannot rule out any differential impact of HFHS on oligodendrocyte loss or proliferation across the gray and white matter after SCI ( Tripathi and McTigue, 2007 ; Vigano et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In spinal cord gray matter by contrast, we observed increased Olig2+ OPCs in mice consuming HFHS at 14 and 30 dpi. Since prior studies have shown that the central canal region is a potential source of OPCs ( Gao et al, 2015 ), it is possible that the increase in Olig2+ OPCs in spinal cord gray matter after SCI, but the reduction in white matter, reflects an impairment in the migration of newly generated OPCs. Also, we cannot rule out any differential impact of HFHS on oligodendrocyte loss or proliferation across the gray and white matter after SCI ( Tripathi and McTigue, 2007 ; Vigano et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, one component of cigarettes, was attributed both pro- and anti-inflammatory effects on the immune system. Its signaling pathway [25,26,27] and cellular response has been investigated in several autoimmune diseases (for review [28]), including EAE [29,30]. The cholinergic system dampens the peripheral immune response indicating the involvement of the α7- nicotinic acetylcholine receptor (nAChR) [25,26], which is found both on neurons and the microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 200 mg/ml nicotine hydrogen tartrate salt in drinking water induced mild, delayed, and chronic clinical signs and less inflammation in MOG 35-55 -induced female C57BL/6 mice (108). Nicotine (28 days, infusion rate of 0.25 ml/h, mini-osmotic pumps) was protective against experimental autoimmune encephalomyelitis by reducing nestin expression, partially allowing for the proliferation (Ki67 + ) of ependymal cells in areas of inflammation and increasing mature anti-inflammatory M2 subtype microglia (NG2 + and CC1 + ) to promote disease recovery (105,109). Nicotine also distinctively affected microglial viability, activation, and function, contrary to non-nicotine cigarette components, especially acrolein that has cytotoxic effects on microglia (105).…”
Section: Anti-inflammatory Effect Of Nicotine On Multiple Sclerosismentioning
confidence: 99%